Peningkatan Kreativitas Santri Pondok Pesantren Ash-Shiddiqi Melalui Pelatihan Landing Page Serta Leadership dan Kepemimpinan - Meliyanti; Suwandi S (Pusat Studi Teknologi Informasi Fakultas Ilmu Komputer Universitas Bandar Lampung, 2026)
Islamic boarding schools play an important role in shaping the character and competencies of young generations; however, limitations in technological mastery and soft skills among students are still evident. This community service activity aims to enhance the creativity and work readiness of students at Ash-Shiddiqi Islamic Boarding School through training in landing page development, Microsoft Office, and leadership. The methods used include training sessions, hands-on practice, mentoring, and evaluation over an eight-month period. The results indicate an improvement in students’ abilities in utilizing technology, managing administrative data, as well as communication and leadership skills. In addition, students were able to produce simple landing pages as a medium for promotion and creativity development. Therefore, this activity has proven to be effective in improving students’ work readiness and increasing the competitiveness of Islamic boarding school graduates.